Understanding African swine fever outbreaks in domestic pigs in a sylvatic endemic area: The case of the South African controlled area between 1977–2017 - (:unkn) unknown (My University, 2020)
South Africa declared a controlled area for African swine fever (ASF) in 1935, consisting of the northern parts of Limpopo, Mpumalanga, North West and Kwa-Zulu Natal Provinces. The area was delineated based on the endemic presence of the sylvatic cycle of ASF, involving warthogs and argasid ticks. Occasionally, spillover occurs from the sylvatic cycle to domestic pigs, causing ASF outbreaks. In the period 1977 to 2017, 59 outbreaks of ASF were reported in domestic pigs within the ASF controlled area of South Africa. During these outbreaks, at least 4,031 domestic pigs either died or were culled. Season did not affect the number of reported ASF outbreaks, but the number of reported outbreaks in this area per year was thought to be slowly increasing, although not statistically significant. Outbreaks occurred predominantly in Limpopo province (93%) and were mostly due to contact (or suspected contact) with warthog or warthog carcasses. Clustering analysis of outbreaks found that the local municipalities of Ramotshere Moiloa, Lephalale and Thabazimbi had the highest relative risk for outbreaks. In 32 of the 59 outbreaks, the genotype of the ASF virus (ASFV) involved could be determined. Phylogenetic analysis of ASFVs detected in domestic pigs during the study period revealed that p72 genotypes I, III, IV, VII, VIII, XIX, XX, XXI and XXII had been involved in causing outbreaks within the ASF controlled area. No outbreaks were reported in the Kwa-Zulu Natal part of the controlled area during this period. South Africa is unlikely to eradicate all sources of ASFV as spillover from the sylvatic cycle in the controlled area continued to occur, but with the implementation of appropriate biosecurity measures pigs can be successfully farmed despite the presence of ASFV in African wild suids and soft ticks.
Keywords: African Research